MODEL PEMBELAJARAN READING ROLLING TEXT DALAM PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Saebani (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The success of learning History of Islamic Culture (SKI) can beinfluenced by many factors one of which is the method of learning. Infact the actual learning of SKI is not difficult, but many students whohave less satisfactory learning outcomes in the lesson SKI. From thiscondition the authors try to use the Reading Rolling Text method(RRT) in the learning of SKI. The sample used in this study is theClass VIII Junior High School Students Al-Firdaus MertoyudanMagelang District, which amounted to 25 students. Data analysisusing descriptive analysis and parametric inferential statisticalanalysis with paired sample t test statistic. Test paired sample t test isa test conducted where the same sample but has two different data. Theresults of this study show that the use of RRT methods in SKI learningcan improve learning outcomes.